The Relationships among Exercise Behavior, Body Composition and Perceived Health Levels in University Students - Levent Sangün; Dilek Sevimli; Tuğba Uluer (Türk Spor ve Egzersiz Dergisi)
Aim and Scope: Increasing physical activity level is important for public health. This study aims to investigate the relationship between regular physical activity level, body composition and perceived health levels of university students. Methods: Participants of this study were consisted of 331 university students including 158 females and 173 males. The mean ages were 21.85 years for females and 22.94 years for males, respectively. The Exercise Behavior Stages of Change Questionnaire was used to determine the physical activity level. Mann Whitney U test was used to compare two genders while Spearman rank order correlation was performed to test the relationship among variables. Findings: Results of our study showed that there are significant differences between males and females in all variables except age and exercise behavior stages. While the exercise behavior stages and perceived health level of those who exercise in females are significantly different from those of sedentary, height and exercise behavior level in males are more statistically significant in favor of those who exercise. While the health level in females is positively related to the age variable and negatively related to the BMI, there was no significant difference between the health and exercise level and other variables in males. Conclusion: As a result, it can be concluded that male and female university students do not engage in regular physical activity at a level that will affect their perceived health levels.